Management of patients with ocular manifestations in vesiculobullous disorders affecting the mouth. (17th November 2016) - Hansen, MS; Klefter, ON; Julian, HO; Lynge Pedersen, AM; Heegaard, S
Abstract : Pemphigoid and pemphigus diseases as well as Stevens–Johnson syndrome present as vesiculobullous disorders of the skin and may additionally involve both the oral cavity and the ocular surface. Ocular involvement ranges from mild irritation and dry eye disease to chronic conjunctivitis, symblepharon, eyelid malposition, ocular surface scarring and severe visual loss. In addition to diagnostic assessments, ophthalmologists must treat the dry eye and meibomian gland dysfunction components of these diseases using a stepladder approach, including eyelid hygiene and lubricants. Topical anti‐inflammatory therapy is used to treat acute inflammatory exacerbations of the ocular surface, but it cannot prevent scarring alone. Intralesional antimetabolite therapy can cause regression of conjunctival pathology in selected cases. Hence, patients with vesiculobullous disorders should be managed by a multidisciplinary team representing ophthalmology, dermatology, otolaryngology, oral medicine and pathology, internal medicine and intensive care. Systemic treatments including corticosteroids, azathioprine, cyclophosphamide, cyclosporine and mycophenolate mofetil help control inflammation. Intravenous immunoglobulins, plasmapheresis and targeted antibody therapy can be used in selected, severe and treatment‐resistant cases. Local surgical management may include debridement of pseudomembranes, lysis of symblepharon, amniotic and mucous membrane grafting as well as reconstructive procedures. Prospective, multicentre, international studies are recommended to further support evidence‐based practice.